2017
DOI: 10.2147/cwcmr.s140673
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice for pressure injury prevention among care managers in a home care setting: a cross-sectional study

Abstract: Purpose: Previous studies on pressure injury prevention using questionnaire surveys have targeted physicians and nurses working in hospitals. However, few have administered surveys to social welfare professionals at home care. Thus, this study aimed to investigate the current level of knowledge and practice regarding pressure injury prevention among Japanese care managers. Patients and methods: A cross-sectional study among care managers working in a Japanese city was performed from June to July 2016. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
3
6
1
Order By: Relevance
“…31 Most care managers currently believe that physician and/or nurse interventions can be initiated after the development of pressure injury, which is not ideal in real-world settings. 16 We therefore believe that pressure injury risk assessment scales, including the PPRA-Home, can serve as a bridge between medical and social welfare professionals to achieve a multidisciplinary approach in preventing pressure injuries during home care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Most care managers currently believe that physician and/or nurse interventions can be initiated after the development of pressure injury, which is not ideal in real-world settings. 16 We therefore believe that pressure injury risk assessment scales, including the PPRA-Home, can serve as a bridge between medical and social welfare professionals to achieve a multidisciplinary approach in preventing pressure injuries during home care.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous questionnaire survey targeting care managers, one type of professional occupation under the social welfare services of the LTCI system, revealed that less than half of the participants found it difficult to use the Braden or OH scales in daily actual clinical practice. 16 Reports have shown that the Braden scale did not have a strong enough impact for use in long-term care facilities. 17 , 18 The Japanese government had originally introduced a medical-social welfare networking model into the LTCI system with care managers as gatekeepers.…”
Section: Introductionmentioning
confidence: 99%
“…However, Japanese care managers generally do not consult with physicians and nurses about pressure injury prevention prior to their home-care clients actually developing pressure injuries. 19 This lack of communication likely is due to the fact that most care managers believe medical professional input and intervention is not needed until after a pressure injury has formed.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, acute care and social welfare professionals have distinct perspectives, not the least of which is their differing clinical environments. 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation